ULTRASOUND DIAGNOSTIC OF MUSCULUS MASSETER - Mariana Dimova-Gabrovska; Desislava Dimitrova (Peytchinski Publishing, 2017)
Ultrasonography is a safe and non-invasive method of imaging organs and structures of the human body. The resulting images are detailed, easily reproducible and received in real time. The aim of this review is to investigate and present the diagnostic capabilities of ultrasonography in the diagnosis of m. masseter in norm and pathology. Survey material is the data from 21 literary sources, selected from 110, found by keywords from January to April 2017. The material of the review is based on the scientific data for ultrasonic imaging of normal anatomy of m. masseter and common pathologies such as: hypertrophy, bruxism, traumas, hemangiomas, cysticercosis, etc. In conclusion, the high diagnostic value of ultrasonography of m. masseter is confirmed in both conditions - norm and pathology. The method is considered safe, easy and effective, which can be of great benefit to the dentists, especially in the case of a difficult diagnosis.